1997
DOI: 10.1042/bj3240935
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cathepsin D activity in retinal pigment epithelial cells

Abstract: This project used retinal pigment epithelial (RPE) cells to investigate the effects of up- and down-regulation of cathepsin D expression on the processing of cathepsin D and on the normal phagocytic and digestive function of these cells. RPE cells were transfected with a pHbetaApr-1-neo vector construct carrying the full-length sequence of the translated region of human cathepsin D in sense and antisense directions. Transfected cells were characterized for the presence and expression of the transgene by PCR am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 23 publications
(30 reference statements)
2
54
0
2
Order By: Relevance
“…proenzyme that is subsequently converted to a 46-kDa intermediate (54,55) and eventually an active 34-kDa enzyme during transport through the secretory pathway to lysosomes (56 -59). To determine whether loss of MREG alters Cat-D function in vivo, enzyme activity, expression levels, and distribution profiles were analyzed in RPE within retinas of Mreg Ϫ/Ϫ and Mreg ϩ/ϩ mice.…”
Section: Loss Of Mreg Results In Decreased Cathepsin D Levels and Actmentioning
confidence: 99%
See 2 more Smart Citations
“…proenzyme that is subsequently converted to a 46-kDa intermediate (54,55) and eventually an active 34-kDa enzyme during transport through the secretory pathway to lysosomes (56 -59). To determine whether loss of MREG alters Cat-D function in vivo, enzyme activity, expression levels, and distribution profiles were analyzed in RPE within retinas of Mreg Ϫ/Ϫ and Mreg ϩ/ϩ mice.…”
Section: Loss Of Mreg Results In Decreased Cathepsin D Levels and Actmentioning
confidence: 99%
“…Ingested phagosomes are normally cleared from the apical RPE to the basal region as phagolysosomes are formed. Cat-D plays a major role in the degradation of opsin in phagolysosomes (30,53,54,60). In these next studies, we quantified the relative levels of opsin and Cat-D in phagosomes by double immunogold labeling of Mreg ϩ/ϩ and Mreg Ϫ/Ϫ retinas (Fig.…”
Section: Loss Of Mreg Results In Decreased Cathepsin D Levels and Actmentioning
confidence: 99%
See 1 more Smart Citation
“…However, strong cathepsin D but not cathepsin B expression was localized in the developing retinal pigment epithelium (RPE). In this regard cathepsin D is considered one of the most important lysosomal enzymes in RPE cells (Regan et al, 1980;Rakoczy et al, 1997), and plays a major role in degradation of the phagocytosed photoreceptors during their renewal process (el-Hifnawi, 1995). Several reports have described cathepsin D in the adult RPE of mammals (Wilcox, 1988;Ortego et al, 1997;Yamada et al, 1990;Rakoczy et al, 1999;Frohlich and Klessen, 2001;Wasselius et al, 2003;Ahuja et al, 2008) and, in concordance with our findings, Hayasaka and Shiono (1982) showed that, with the exception of cathepsin D displaying high levels of activity, most of the lysosomal enzyme activities detected in the rabbit RPE were low at birth.…”
Section: Spatiotemporal Expression Of Cathepsin B and D Genes: Relatimentioning
confidence: 99%
“…There is evidence that tamoxifen, toremifene and chloroquine reduce the activities of cathepsin D and N-acetyl-b-glucosaminidase in retinal pigment epithelial cells (Toimela et al 1998). Cathepsin D is essential in rod outer segment digestion by human retinal pigment epithelial cells (Kennedy et al 1994;Rakoczy et al 1997). As a weakly basic compound, chloroquine accumulates in lysosomes, raising the lysosomal pH, which leads to inhibition of lysosomal enzymes (Ohkuma & Poole 1981;Toimela et al 1998;Schraermeyer et al 1999).…”
Section: Discussionmentioning
confidence: 99%